# Qm - Hermitian Commutator [A,B]†

I have this review question: If operators A and B are hermitian, prove that their commutator is "anti-hermitian", ie) [A,B]†=-[A,B]

What has me confused is the placement of the dagger on the commutator. Why [A,B]† and not [A†,B†]? Also, I am using Griffith's Intro to QM as a text. I have failed to find where the author uses this [A,B]† commutator in the book. If anyone has the book and can give me a page number of an example, I'd be grateful.

Last edited:

Related Advanced Physics Homework Help News on Phys.org
George Jones
Staff Emeritus
Gold Member
What does $\left[ A , B \right]$ equal?

Dick
Homework Helper
[A,B]=AB-BA. Just use that. You don't need any book references.

What does $\left[ A , B \right]$ equal?
[A,B] = AB - BA

So, [A, B]† = (AB - BA)† = (AB)† - (BA)† = B†A† - A†B†

and [A†,B†] = A†B† - B†A†.

I think there may be some confusion. I know what [A,B] is; What I'm inquiring on is the placement of the dagger.

Edit: You guys can see my dagger symbol, right?

George Jones
Staff Emeritus
Gold Member
So, [A, B]† = (AB - BA)† = (AB)† - (BA)† = B†A† - A†B†
Also,
operators A and B are hermitian

dextercioby